PERSEPSI MASYARAKAT TERHADAP FENOMENA HOAX DI MEDIA ON LINE PADA ERA POST TRUTH - Amalia Amalliah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
Social media has become a companion in the daily life of the community, both among adolescents and adults. All the news that happened at that time or that was phenomenal or wanted to meet with friends, distant relatives, we could easily find out the whereabouts and the news or activities carried out. Social media is a necessity for all Indonesians, the news contained in social media, especially news that is phenomenally uploaded, quickly spreads into unfiltered, even difficult to distinguish between original and false news. This requires the intelligence and thoroughness of the community in responding to it. Hoax, now is a necessity that must be faced by people in this digital era. The production of false or false news cannot be separated from the post-truth phenomenon, where truth is no longer based on facts but on a subjective perspective (politics, religion, class, etc.). This phenomenon has placed the community in a situation of mutual suspicion. The audience can no longer tell which news or information is valid, which one is a hoax. This study was arranged using descriptive research methods. The results of this study are then processed and analyzed for the appearance of conclusions. And also use the Theory of Selective Process in Mass Communication which consists of. Selective exposure, selective retention and Selective perception. Ethics is a moral compass in dealing with gray situations and a dilemma due to the situation. Anyone who uploads news must ensure that his actions always maximize the search for truth and minimize the impact of losses on others. Social media ethics means being committed to doing things right when the possibility of error is greater.